2000
DOI: 10.1523/jneurosci.20-16-06241.2000
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Anatomical Organization of Multiwhisker Response Interactions in the Barrel Cortex of Rats

Abstract: To understand the physiological properties and anatomical organization of the spatiotemporal interaction of the responses to multiwhisker stimulation in neurons of the rat barrel cortex, single-unit recordings of 114 neurons were performed across all layers (layer II/III, n ϭ 39; IV, n ϭ 33; V/VI, n ϭ 42) of the posteromedial barrel subfield of the primary somatosensory cortex of anesthetized rats. Two neighboring principal and adjacent whiskers (PW and AW, respectively) in the same row were deflected rostrall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 39 publications
7
92
3
Order By: Relevance
“…Despite the predominance of suppressive interactions that we have observed, previous studies on the spatiotemporal sensory integration performed by barrel cortex neurons have reported the presence of facilitatory interactions between the responses for different whiskers (Ghazanfar and Nicolelis 1997;Ghazanfar et al 2000;Shimegi et al 1999Shimegi et al , 2000. Notably, the work by Shimegi and colleagues, using very similar procedures to those applied here (anesthesia, unit recording, frequency of stimulation, choice of ISIs), has described a much higher incidence of supralinear summation for 0.5-Hz stimulation than what we have observed.…”
Section: Incidence Of Supralinear Interactions For Stimulation At a Lcontrasting
confidence: 60%
See 4 more Smart Citations
“…Despite the predominance of suppressive interactions that we have observed, previous studies on the spatiotemporal sensory integration performed by barrel cortex neurons have reported the presence of facilitatory interactions between the responses for different whiskers (Ghazanfar and Nicolelis 1997;Ghazanfar et al 2000;Shimegi et al 1999Shimegi et al , 2000. Notably, the work by Shimegi and colleagues, using very similar procedures to those applied here (anesthesia, unit recording, frequency of stimulation, choice of ISIs), has described a much higher incidence of supralinear summation for 0.5-Hz stimulation than what we have observed.…”
Section: Incidence Of Supralinear Interactions For Stimulation At a Lcontrasting
confidence: 60%
“…Additionally, unit recording (ArmstrongJames and Fox 1987;Simons 1978) and optical imaging (Kleinfeld and Delaney 1996) studies have reported activity patterns in the barrel cortex following single-whisker deflections elongated along rows. In line with those results, electrophysiological investigations have mainly tested multi-whisker integration along rows (Carvell and Simons 1988;Shimegi et al 1999Shimegi et al , 2000Simons 1985;Simons and Carvell 1989; but see also Mirabella et al 2001). However, a supralinear interaction most prominent for whiskers located in the same arc was recently described (Ghazanfar and Nicolelis 1997), suggesting that modulatory influences could exist both in the rostrocaudal and dorsoventral directions.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations